PENGEMBANGAN MEDIA SIMULATOR PADA PENDIDIKAN DAN PELATIHAN FOAM TENDER OPERATION AND DEFENSIVE DRIVING DI BALAI PENDIDIKAN DAN PELATIHAN PENERBANGAN PALEMBANG - Asep Muhamad Soleh (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study produced a simulator for education and training in Foam Tender Operation and Defensive Driving and to find out whether learning outcomes using simulators are better than students who do not use simulators. The study uses the Research and Development (R & D) method. The research was conducted at the Palembang Aviation Training and Training Center on students in Foam Tender Operation and Defensive Driving, Aviation Accident Aid and Fire Fighting (PKP-PK). The trial design used was quasi-experimental post-test only control group design. The findings of the study, namely the simulator learning media categorized as very feasible to use in learning with a percentage value of 81.67%. Student responses after using simulators are categorized very well with a percentage of 85%. Students who are taught using media or experimental classes have better learning outcomes by obtaining greater scores than students who do not use simulators. From the results above, it can be said that the development of simulator learning media is feasible to use and the response of students using simulator learning media is very good.